Fundamental Data Mining Techniques for Declarative Process Mining - Grohmann, Nico (2022)
Process mining is a Business Process Management (BPM) technique that uses execution data of business processes for their analysis. By transforming the data to so-called event logs, process mining tools generate process models that describe the executions as close as possible. Process discovery can result either in graph-based notations (e.g., Petri nets or BPMN) or declarative ones like Declare. One hypothesis in this work is that declarative constraint templates can support model understanding in case process mining results in large, confusing “spaghetti” diagrams. Overall, this work contributes an approach including a prototypical implementation for applying association rule and sequential pattern mining to event logs for discovering declarative process models. Preprocessing steps and the transformation of rules and patterns to constraints in Declare are addressed explicitly. In this way, analysts receive transparent insights into the basis of the overall declarative model.Process Mining ist eine Technik des Geschäftsprozessmanagements, die Ausführungsdaten von Geschäftsprozessen zur Analyse verwendet. Durch eine Bereitstellung der Daten in sogenannten Event-Logs generieren Process Mining-Tools Prozessmodelle, die die Ausführungen möglichst präzise beschreiben. Dies kann entweder in graph-basierte Notationen wie Petri-Netze oder BPMN oder deklarative Notationen wie Declare resultieren. Eine Hypothese der Arbeit ist, dass deklarative Constraints die Verständlichkeit der Modelle erhöhen kann wenn Process Mining große, unübersichtliche „Spaghetti-Diagramme“ produziert. Diese Arbeit präsentiert einen Ansatz inklusive prototypischer Implementierung um Assoziations- und Sequenzmusteranalyse auf Event-Logs anzuwenden, mit dem Ziel, deklarative Prozessmodelle zu erzeugen. Auf Preprocessing-Schritte und die Übersetzung der Regeln und Muster zu Declare-Constraints wird explizit eingegangen. Dadurch erhalten Analysten transparente Einblicke in die Basis des gesamten deklarativen Modells.Permalinkhttps://nbn-resolving.org/urn:nbn:de:hbz:6-54059510537 ISBN978-3-487-16155-6 (Druckausgabe Georg Olms Verlag)978-3-8405-0266-8 (elektronische Version)Paperback, XVII, 223 Seiten